Pengaruh metode Short Messaging Service (SMS) terhadap kepatuhan menelan Obat Anti-TB - Susan Susyanti; Hanna Rizmadewi Agustina (Jurnal Medika Cendikia, 2014)
One factor that plays an important role for the treatment of tuberculosis (TB) is TB patient adherence factor itself. TB recurrence rates showing an increase of about 2.5 times that indicate a problem both from a medical aspect, immunological and psychological patients. SMS method is one of the alternative methods that can be used to remind patients with TB disease of anti-tuberculosis drugs ingest on a regular basis. The purpose of this review is to describe a variety of nursing and or health literature that discussed the cellular-based communication using SMS in patients with TB in improving adherence to swallow anti-tuberculosis drugs, and then to critically evaluate the evidence available to support nursing practice of the community, especially related to health promotion. Data collected in the form of journal literature published research, traced using EBSCOhost-CINAHL, ProQuest, PubMed, HealthMed Journal, etc. by using the key word "Short Messaging Service (SMS)", "patient compliance" "tuberculosis (TB)", and in between. Ultimately as many as 15 articles found in publications of the 2000s, between 2005 to 2013. In general, the results of all the literature in the review shows that patients who received SMS showed significant improvement in swallowing compliance of anti-tuberculosis drugs. Conclusions from the literature review, the SMS method can be used as one effective medium for improving patient compliance with tuberculosis